DIGITALISASI GUA PRASEJARAH BERGAMBAR DI KAWASAN KARST MAROS-PANGKEP: STUDI KASUS LEANG LAMBATORANG KABUPATEN MAROS - Ilyas, Imran; Nur, Muhammad; Alimuddin, Ilham; Tahir Muda, Khadijah (JURNAL ILMU BUDAYA, 2023)
The Maros and Pangkep areas contain a number of damaged caves that require immediate attention. Preserving our cultural heritage demands documentation, mapping, and modeling. The utilization of 3D visualization is paramount in recording cultural heritage data. Moreover, it contributes to the conservation, rehabilitation, and maintenance of historical structures. In the current era of scientific and technological advancements, laser scanners have made rapid progress. The data generated by these scanners plays a critical role as a backup to safeguard cultural heritage objects in case of damage, destruction, or loss. The benefits of employing 3D visualization lie in its ability to create detailed and integrated models, resulting in a comprehensive database accessible to all stakeholders. This study utilized the Block Bundle Adjustment methodology to map the prehistoric cave Leang Lambatorang and create a 3D visualization using a laser scanner. The research findings include the 3D visualization of the data from Leang Lambatorang